Selective serotonin reuptake inhibitors and venlafaxine in early pregnancy and risk of birth defects: Population based cohort study and sibling design - Furu, Kari; Kieler, Helle; Haglund, Bengt; Engeland, Anders; Selmer, Randi; Stephansson, Olof; Valdimarsdottir, Unnur Anna; Zoega, Helga; Artama, Miia; Gissler, Mika; Malm, Heli; Nørgaard, Mette (BMJ, 2016)
Objective To assess whether use of specific selective serotonin reuptake inhibitors (SSRIs) or venlafaxine in early pregnancy is associated with an increased risk of birth defects, with emphasis on cardiovascular birth defects even when accounting for lifestyle or other familial confounding. Design Multicountry population based cohort study, including sibling controlled design. Setting Nordic population (Denmark, Finland, Iceland, Norway, and Sweden) identified from nationwide health registers at different periods in 1996-2010. Population The full study cohort included women giving birth to 2.3 million live singletons. The sibling cohort included 2288 singleton live births. The sibling controlled analyses included sibling pairs who were discordant for exposure to SSRIs or venlafaxine and birth defects. Main outcome measure Prevalence of birth defects, including subtypes of cardiac defects. Odds ratio of birth defects from logistic and conditional logistic regression. Results Among 36 772 infants exposed to any SSRI in early pregnancy, 3.7% (n=1357) had a birth defect compared with 3.1% of 2 266 875 unexposed infants, yielding a covariate adjusted odds ratio of 1.13 (95% confidence interval 1.06 to 1.20). In the sibling controlled analysis the adjusted odds ratio decreased to 1.06 (0.91 to 1.24). The odds ratios for any cardiac birth defect with use of any SSRI or venlafaxine were 1.15 (95% confidence interval 1.05 to 1.26) in the covariate adjusted analysis and 0.92 (0.72 to 1.17) in the sibling controlled analysis. For atrial and ventricular septal defects the covariate adjusted odds ratio was 1.17 (1.05 to 1.31). Exposure to any SSRI or venlafaxine increased the prevalence of right ventricular outflow tract obstruction defects, with a covariate adjusted odds ratio of 1.48 (1.15 to 1.89). In the sibling controlled analysis the adjusted odds ratio decreased to 0.56 (0.21 to 1.49) for any exposure to SSRIs or venlafaxine and right ventricular outflow tract obstruction defects. Conclusions In this large Nordic ...